Pengaruh Kualitas Produk, Harga dan Layanan Produk Terhadap Keputusan Pembelian dan Loyalitas Pelanggan B2B PT. TCM - Pardomuan S, Ernst Tunggul; Sabar, Sabar; Wijayaningtyas, Maranatha (Syntax Corporation, 2025)
Business competition in the palm oil industry causes customer loyalty to be an important factor to maintain business continuity. The authors examine the factors that influence customer purchase intent and its relationship with customer loyalty. The researcher sees the influence of the relationship between Product Quality, Goods Price and Service Quality and the influence of moderation factors from the Payment System on Customer Purchase Intention and Influence Customer Loyalty. In the results of this study, Product Quality and Quality Perceived by Buyers Affect Customer Purchase Intentions. The Payment System strengthens Product Quality to the Customer's buying interest, Purchase intention affects loyalty. While Product Prices and Product Services do not affect Customer Purchase Intention and Ease of Payment is unable to moderate Product and Product Service Prices against Purchase Intentions. This study discusses the relationship between the influence of payment systems on buying interest and customer loyalty in the palm oil industry. This article will contribute literature in palm oil marketing and will simultaneously help the company to maintain customer loyalty.